Dietary glycemic index and glycemic load and risk of colorectal cancer: results from the EPIC‐Italy study. Issue 12 (25th November 2014) - Sieri, S.; Krogh, V.; Agnoli, C.; Ricceri, F.; Palli, D.; Masala, G.; Panico, S.; Mattiello, A.; Tumino, R.; Giurdanella, M.C.; Brighenti, F.; Scazzina, F.; et al.
<x xml:space="preserve">Abstract</x> A carbohydrate‐rich diet, resulting in high blood glucose and insulin, has been hypothesized as involved in colorectal cancer etiology. We investigated dietary glycemic index (GI) and glycemic load (GL), in relation to colorectal cancer, in the prospectively recruited EPIC‐Italy cohort. After a median 11.7 years, 421 colorectal cancers were diagnosed among 47, 749 recruited adults. GI and GL were estimated from validated food frequency questionnaires. Multivariable Cox modeling estimated hazard ratios (HRs) for associations between colorectal cancer and intakes of total, high GI and low GI carbohydrate and GI and GL. The adjusted HR of colorectal cancer for highest versus lowest GI quartile was 1.35; 95% confidence interval (CI) 1.03–1.78; p trend 0.031. Increasing high GI carbohydrate intake was also significantly associated with increasing colorectal cancer risk (HR 1.45; 95% CI 1.04–2.03; p trend 0.034), whereas increasing low GI carbohydrate was associated with reducing risk (HR 0.73; 95% CI 0.54–0.98; p trend 0.033). High dietary GI and high GI carbohydrate were associated with increased risks of cancer at all colon sites (HR 1.37; 95% CI 1.00–1.88, HR 1.80; 95% CI 1.22–2.65, respectively), whereas high GI carbohydrate and high GL were associated with increased risk of proximal colon cancer (HR 1.94; 95% CI 1.18–3.16, HR 2.01; 95% CI 1.08–3.74, respectively). After stratification for waist‐to‐hip ratio (WHR), cancer was significantly associated with GI, and high GI carbohydrate, in those with high WHR. These findings suggest that high dietary GI and high carbohydrate intake from high GI foods are associated with increased risk of colorectal cancer.